Kolangiokarsinoma dan Infeksi Virus Hepatitis - PRAMONO, LAURENTIUS A. (Indonesian Journal of Cancer, 2015)
ABSTRACTCholangiocarcinoma is a cancer which derived from biliary epithelial. This malignancy is rare, but have poor prognosis. Manifestation of liver flukes, primary sklerosing cholangitis, hepatolithiasis, and malformation of the biliary tree all this time are known to be risk factors for cholangiocarcinoma. In recent years, it has been shown that infection of hepatitis B and hepatitis C viral are also cholangiocarcinogenic, so it is known to become ânewâ risk factor for cholangiocarcinoma. A literature study was conducted to search for pathogenesis theory and evidence in clinical and community study. Most basic, epigenetic, pathologic, clinical, and community studies revealed that there is a link between hepatitis viral infection and intrahepatic cholangiocarcinoma. Unfortunately, the link between the infection and extrahepatic cholangiocarcinoma remain unclear. Look at the analysis, in the future, we must take more attention to chronic hepatitis patients for the risk of getting cholangiocarcinoma, while in cholangiocarcinoma, we must also consider about the risk factors such as hepatitis viral infection in the patients. Keywords: cholangiocarcinoma, hepatitis B, hepatitis C, cholangiocarcinogenicÂ ABSTRAKKolangiokarsinoma adalah kanker yang berasal dari epitel bilier. Keganasan ini termasuk jarang, namun memiliki prognosis yang buruk. Manifestasi cacing hati, kolangitis sklerosis primer, hepatolitiasis, dan malformasi bilier selama ini diketahui merupakan faktor risiko kejadian kolangiokarsinoma. Beberapa tahun terakhir diketahui bahwa infeksi virus hepatitis B dan hepatitis C juga memiliki sifat kolangiokarsinogenik sehingga menjadi faktor risiko âbaruâ bagi kejadian kolangiokarsinoma. Penelusuran literatur mengenai patogenesis dan bukti ilmiah dalam studi klinis dan epidemiologi dilakukan untuk mengkaji hubungan antara infeksi virus hepatitis B dan C dengan kolangiokarsinoma. Sebagian besar riset dasar, epigenetik, patologi, klinis, dan komunitas (populasi) menyiratkan adanya hubungan antara infeksi virus hepatitis B dan C dengan kolangiokarsinoma intrahepatik. Sayangnya, hubungan infeksi kedua virus dengan kolangiokarsinoma ekstrahepatik masih belum jelas. Melihat kajian ini, ke depan perlu perhatian lebih kepada pasien hepatitis kronis terhadap risiko kolangiokarsinoma. Sementara, bagi pasien kolangiokarsinoma, perlu pencarian faktor risiko, yang salah satunya adalah infeksi virus hepatitis kronis.Kata Kunci: kolangiokarsinoma, hepatitis B, hepatitis C, kolangiokarsinogenik